Handbuch Europäische Sprachkritik Online Sprachpurismus und Sprachkritik - Schwinn, Horst (Handbuch Europäische Sprachkritik Online, 2018)
In this third volume of the "Online Handbook of Language Criticism - A European Perspective", linguistic purism is being understood as both criticism of language usage on the level of parole and criticism of forms and structures of a language on the level of langue. The articles in this volume illustrate in comparative perspective in which constellations of languages linguistic purism in German, English, French, Italian, and Croatian was relevant in the past, and still is today, how the individual languages were and are affected by language-puristic activities, and which actors and discourses have formed and framed language-puristic activities in the different language cultures.